2021
DOI: 10.1097/pg9.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Cognitive, and Neuropsychiatric Needs in Children and Young People With Wilson Disease

Abstract: Objective: Wilson disease (WD) is associated with neurological, psychiatric, cognitive, and psychosocial difficulties, but there is little data regarding the nature and prevalence of these problems in children and young people (CYP). Methods: A single-center case-note review to establish the incidence and nature of these issues in CYP with WD, managed before and after multidisciplinary team (MDT) clinics, was established. Results: Out of 69 (43 males) CYP with WD, 37.8% presented with acute liver failure, 48.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Given the rarity of WD, the cohort of children with WD requiring LT in a single-centre study is quite small, which could affect the power of the study, hence it is difficult to be certain that somebody with an index of more than 11 would have survived without LT. A multicentre prospective re-evaluation of WDI is a way forward. Data on noncompliance were not collected as part of this study; however, a recent study from our centre has reported a variable degree of noncompliance in 50% of WD cases (21). It is important to note that a comprehensive mutational analysis using whole exome sequencing should be carried to exclude other conditions mimicking WD like MDR3 disease.…”
Section: Discussionmentioning
confidence: 99%
“…Given the rarity of WD, the cohort of children with WD requiring LT in a single-centre study is quite small, which could affect the power of the study, hence it is difficult to be certain that somebody with an index of more than 11 would have survived without LT. A multicentre prospective re-evaluation of WDI is a way forward. Data on noncompliance were not collected as part of this study; however, a recent study from our centre has reported a variable degree of noncompliance in 50% of WD cases (21). It is important to note that a comprehensive mutational analysis using whole exome sequencing should be carried to exclude other conditions mimicking WD like MDR3 disease.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a time when poor adherence to treatment occurs, and it is important to consider whether any behavioural changes are due to poor control of WD rather than an expected stage of adolescence. 225 Magnetic resonance imaging of the brain to look for characteristic changes could potentially be helpful in identifying the development of neuropsychiatric disease. 226 Clinicians should also be aware of the potential for nutritional deficiencies in iron or zinc and of rarer longterm complications such as Fanconi syndrome or effects of long-term treatment such as Elastosis perforans serpiginosa, which may occur with D-penicillamine use.…”
Section: Bsg Espghan and Easl Have Published Guidelines Regardingmentioning
confidence: 99%
“…There are several potential issues that may affect YAs with WD. This may be a time when poor adherence to treatment occurs, and it is important to consider whether any behavioural changes are due to poor control of WD rather than an expected stage of adolescence 225 . Magnetic resonance imaging of the brain to look for characteristic changes could potentially be helpful in identifying the development of neuropsychiatric disease 226 .…”
Section: Aetiologiesmentioning
confidence: 99%